Charcot-Marie-Tooth disease: New insights from skin biopsy. (6th October 2015) - Manganelli, Fiore; Nolano, Maria; Pisciotta, Chiara; Provitera, Vincenzo; Fabrizi, Gian M.; Cavallaro, Tiziana; Stancanelli, Annamaria; Caporaso, Giuseppe; Shy, Michael E.; Santoro, Lucio
Abstract : Objective: To evaluate, by skin biopsy, dermal nerve fibers in 31 patients with 3 common Charcot-Marie-Tooth (CMT) genotypes (CMT1A, late-onset CMT1B, and CMTX1), and rarer forms of CMT caused by mutations in RAB7 (CMT2B), TRPV4 (CMT2C), and GDAP1 (AR-CMT2K) genes. Methods: We investigated axonal loss by quantifying Meissner corpuscles and intrapapillary myelinated endings and evaluated morphometric changes in myelinated dermal nerve fibers by measuring fiber caliber, internodal, and nodal gap length. Results: The density of both Meissner corpuscles and intrapapillary myelinated endings was reduced in skin samples from patients with CMT1A and all the other CMT genotypes. Nodal gaps were larger in all the CMT genotypes though widening was greater in CMT1A. Perhaps an altered communication between axons and glia may be a common feature for multiple forms of CMT. Internodal lengths were shorter in all the CMT genotypes, and patients with CMT1A had the shortest internodes of all our patients. The uniformly shortened internodes in all the CMT genotypes suggest that mutations in both myelin and axon genes may developmentally impede internode formation. The extent of internodal shortening and nodal gap widening are likely both important in determining nerve conduction velocities in CMT. Conclusions: This study extends the information gained from skin biopsies on morphologic abnormalities in various forms of CMT and provides insights into potential pathomechanisms of axonal and demyelinating CMT.